The Impact of the Great Depression and Social Injustice on American Society in John Steinbeck’s The Grapes of Wrath - Waad Adil Lateef (Genius Journals, 2022)
This paper discusses the subject of racial discrimination and economic inequality between classes of American society during the Great Depression (1929) in John Steinbeck's novel "The Grapes of Wrath". The narrator highlighted the problems faced by farmers and migrant workers through the inhuman and hostile dealings by the financial institutions of the capitalist and bourgeois classes. The events of the novel revolve around the material situation of agricultural workers whose livelihood and dignity have been robbed by machinery and technology. Here, through the Jawad family and their migration to California, the narrator illustrates the suffering that family experienced and the ways they struggled to create a new life at the height of the Great Depression. John Steinbeck presents his main idea in this novel is to support the poor classes and criticize the bourgeois classes and the way they deal with the working classes by starving them and taking away their rights, so the narrator has given an indirect message of revolution against the landowners and owners of capitalist companies and taking rights from them through the character of Tom and a protest against the injustice that occurred society because of the greed of those companies.
Keywords: The Grapes of Wrath; Great Depression; Capitalism; Inhumanity